Perceptions of small, medium and micro enterprises in Johannesburg, Gauteng on the impact of Preferential Procurement Policy Framework Act (Act No.5 of 2000) as a supplier diversity tool - Mahlangu, Ntuthuko (My University, 2016)
This research investigates perceptions of the SMME community in Johannesburg, Gauteng, on the impact of the Preferential Procurement Policy (PPP) Framework Act (Act No. 5 of 2000) as a Supplier Diversity (SD) tool. The research questions discussed are: 1) Are SMMEs directly benefitting from government as a result of PPP? 2) Are SMMEs indirectly benefitting through the private sector as a result of PPP? 3) How can PPP be improved? and 4) What are the problems with the implementation of PPP? The Osiba Research (2011) found that there was minimal impact from government programs in supporting and improving the majority of black-owned SMMEs and integrating them into the mainstream economy. It was further found that the major shortcomings were not due to insufficient or inaccurate policy, but the government’s inability to implement and support the very programs they designed. Other factors that work against SD in South Africa are corruption and nepotism which have led to lack of transparency in the awarding of tenders (Lodge T, 1998). Weak policy coordination and implementation, funding constraints and the fact that policy benefits were leveraged almost exclusively by medium-sized enterprises, which were often white owned, meant that previously disadvantaged people continue to be economically marginalized (Rogerson, 2013). Another setback is that of set-asides. Government has not been practicing its own policy through public procurement and as a result the private sector has showed little commitment to these set-asides. This is partly because the National Treasury holds that set-asides will inflate the cost of procurement (Timm, 2011). This is a qualitative study and as such an interpretivist research approach was used. Enterprises included in the sample were selected using the City of Johannesburg’s Supplier Database, which is the City’s official database that contains the list of accredited prospective suppliers of different goods and services that are required by the City. The results of this research suggests that while there have been links to increased economic growth and rebalancing of socio-economic inequalities as a result of PPP, there are still major problems to overcome such as lack of transparency in awarding tenders, beneficiaries of government business employing non South African citizens/permanent residents, despondency on set-asides, fronting, lack of access to funding, lack of information and lack of commitment to PPP by large corporates. The study concludes with recommendations on policy, how the problem of rationalisation might be overcome, as well as how closer cooperation between SMMEs, government and large corporates can enhance PPP. Recommendations on potential future research are also made.
A Research Report submitted in partial fulfilment of the requirements for the Masters of Management in Entrepreneurship and New Venture Creation
Keywords: Governmenr purchasing--South Africa; Small business--South Africa--Management; Industrial management--South Africa